2017
DOI: 10.1111/jog.13344
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of Duchenne and Becker muscular dystrophies: Underestimated problem of the secondary prevention of monogenetic disorders

Abstract: Carrier status testing in women prior to conception has a positive impact on the frequency of first-trimester prenatal diagnosis and known D/BMD carrier status on the effectiveness of prenatal diagnosis. Due to the low percentage of women tested effectively prior to conception, carrier status testing in the families at risk should be propagated (including possibility of prenatal diagnosis of female fetuses).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, experience shows that in the Netherlands, for example, 78% of girls over 16 years of age have not yet been tested, and the probable cause is that the average age of motherhood is about 28 years of age, so they are tested later [29], while 1/3 of potential carriers are not tested at all [30]. It has been found that only 52.7% of women at risk for DMD/BMD were tested for carrier status before conception [31]. It should be kept in mind that, in addition to the risk of bearing affected offspring, 10% of female carriers develop cardiomyopathy [32,33], so early detection of carrier status would allow adequate cardiac monitoring of these women, which is recommended from the age of 16 [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, experience shows that in the Netherlands, for example, 78% of girls over 16 years of age have not yet been tested, and the probable cause is that the average age of motherhood is about 28 years of age, so they are tested later [29], while 1/3 of potential carriers are not tested at all [30]. It has been found that only 52.7% of women at risk for DMD/BMD were tested for carrier status before conception [31]. It should be kept in mind that, in addition to the risk of bearing affected offspring, 10% of female carriers develop cardiomyopathy [32,33], so early detection of carrier status would allow adequate cardiac monitoring of these women, which is recommended from the age of 16 [34].…”
Section: Discussionmentioning
confidence: 99%